Abnormal surges and the effects of the Seto Inland Sea circulation in Hiroshima Bay, Japan - Jeong, Jae-Soon; Lee, Han Soo; Mori, Nobuhito (Frontiers in Marine Science, 2024)
The Seto Inland Sea (SIS) is the largest semienclosed coastal sea in Japan and has three connections with the outer seas. When a typhoon approached the SIS in September 2011, spatial variations of sea level elevation were observed across the SIS. Additionally, an unusual sea level rise (abnormal surge) occurred in Hiroshima Bay approximately 8 days after the typhoon passed, with the Itsukushima Shrine in the bay flooded by the surge. To understand the mechanism of the abnormal surge in the bay and the relationship between sea level variations and circulation in the SIS, we investigated the 2011 event by applying a high-resolution numerical ocean circulation model using SCHISM with bias correction for sea surface heights (SSHs) at the open boundary. The overall easterly throughflow due to the west-high east-low SSH pattern in the SIS and temporary SSH disturbances due to typhoons were well reproduced in the model results. Among the three connections, the Bungo Channel mainly determined the overall net flux into the SIS and contributed significantly to sea level variations within the SIS. Additionally, the Kii Channel played more crucial roles in shaping the circulation and local sea level variations. The Kanmon Strait exhibited minor impacts. The abnormal tide in Hiroshima Bay was mainly attributed to seawater flux input from the outer seas, in conjunction with the subtidal internal seiche with the bay. The results will help us to further understand the physical processes of the ocean and establish evidence-based safety plans for reducing natural hazard damage.